Loss of Cultural Meaning in Netflix’s Gadis Kretek Indonesian-English Translation - Wulandari, Putu Gita Putri; Sosiowati, I Gusti Ayu Gde; Laksminy, Luh Putu (Lexicon, 2025)
This study investigates the phenomenon of information loss in the Indonesian-English translation of cultural terms in the Netflix series Gadis Kretek (Cigarette Girl), focusing on how key cultural nuances are reduced or omitted in the translation process. The study highlights the challenges faced when rendering culturally embedded into English, raising concerns about accuracy and cultural authenticity. This study used comprehensive semantic-componential analysis, guided by Larson’s Componential Analysis (1998) and Nida and Taber’s theory of Loss and Gain of Information (1982), applied specifically to Indonesian cultural contexts in audiovisual translation. Utilising qualitative methodologies, such as documentation, observation, and linguistic comparison, the study uncovers significant semantic reductions, including the omission of cultural values, historical context, and social connotations. The causes of these losses are considered to be primarily attributed to a lack of specificity in English, cultural and social gaps, and structural differences between the languages. In conclusion, the study emphasises the necessity for culturally sensitive translation strategies, with the core finding being that linguistic equivalence alone is insufficient to preserve cultural depth in cross-cultural translations.